A qualitative study of urban hospital transitional care - Joe Feinglass; Samuel Wein; Caroline Teter; Christine Schaeffer; Angela Rogers (Qualitative Research in Medicine & Healthcare, 2018)
This study is part of a mixed methods evaluation of a large urban medical center transitional care practice (NMG-TC). The NMG-TC provides integrated physical and behavioral health care for high need patients referred from the hospital emergency department or inpatient units and who lack a usual source of primary care. The study was designed for internal quality improvement and sought to evaluate staff perceptions of successful transitions for their medically and socially complex patients, and alternatively, the obstacles most likely to negatively impact patient outcomes. All 16 NMG-TC patient care staff were interviewed in a collaborative effort to produce empowered testimony that might go beyond expected clinical narratives. The interview schedule included questions on risk stratification, integrated mental health care, provider to provider handoffs, and how staff deal with key social determinates of patients’ health. The constant comparative method was used to deductively derive themes reflecting key domains of transitional care practice. Seven themes emerged: i) the need to quickly assess patient complexity; ii) emphasizing caring for major mental health and substance use issues; iii) obstacles to care for uninsured, often undocumented patients; iv) the intractability of homelessness; v) expertise in advancing patients’ health literacy, engagement and activation; vi) fragmented handoffs from hospital care and vii) to primary care in the community. Respondent stories emphasized methods of nurturing patients’ self-efficacy in a very challenging urban health environment. Findings will be used to conceptualize pragmatic, potentially high-impact transitional care quality improvement initiatives capable of better addressing frequent hospital use.